Development of E-Books Based on 4C Skills Through a Differentiation Approach to Science Learning - Nurhayati Nurhayati; Tirtawaty Abdjul; I Made Hermanto; Muhammad Yunus (Postgraduate, University of Mataram, 2025)
E-books are essential in developing 4C skills and differentiated learning because they offer accessibility and flexibility that support students' diverse learning styles. In addition, they allow customization of teaching materials according to students' needs, which increases motivation and learning independence. This research aims to develop an e-book based on 4C skills through a differentiated approach to valid, practical science learning. This study falls within the development research category that uses the ADDIE model. With an average validation score of 3.73, this e-book falls into the “very valid” category. In practical terms, this media is easy for teachers and students to use, fits the learning plan, and shows a learning implementation rate of 90%. Student responses were very good, with an average of 89.79% for four evaluation indicators, showing great benefits and a high level of satisfaction in the learning process. Overall, the e-book based on 4C developed through a differentiated approach to science learning can be categorized as valid and practical because it can increase student involvement in learning. In addition, interactive features in e-books support communication and collaboration between students, allowing them to share ideas and opinions. E-books also enable teachers to adapt material to individual needs so each student can learn at the pace and style they desire.